Loyalty Cards And Personal Information - Themistocleous, Christos (My University, 2018)
Loyalty schemes are considered to be integral parts in the development of customer loyalty for companies within different sectors. For example, supermarkets within the Cypriot industry like Carrefour, Metro and Alfamega have in place loyalty cards while bonus or club cards are also present in retail industries like Stephanis – or even within the hospitality sector with Starbucks and Costa coffee rewards cards. Even though the name of these schemes might differ from case to case – from loyalty, rewards or membership cards – they are all examples of loyalty schemes that seek to maximise the buy-rebuy behaviour of customers through a strategy of “grow and retain”, also known as customer loyalty.
Keywords: Customer Data; Privacy